FAKTOR–FAKTOR YANG MEMPENGARUHI KINERJA BISNIS HOTEL DI KECAMATAN BATURRADEN, PURWOKERTO, SETELAH MENGHADAPI COVID19 - Mukaromah, Syifa Kemala; Kusumastati, Widyahayu Warmmeswara; Arofah, Triani (Universitas Trilogi, 2023)
This study aimed to analyze the positive effects of human capital, structural capital, relational capital, and pricing capability on the business performance of hotels in Baturraden District after facing the impact of COVID-19, namely the 2020-2022 period. The population in this study were all hotels in Baturraden District, Banyumas Regency, namely 113 hotels. Purposive sampling method was used in determining the sample so that the number of samples was determined as many as 72 hotels. The data collection method used a printed questionnaire and obtained 53 respondents. The research approach used a quantitative approach. The data analysis technique was performed using multiple linear regression using the SPSS 26 application. The results of the analysis show that: (1) human capital has a positive and significant effect on business performance, (2) structural capital has no effect on business performance, (3) relational capital has a positive effect and significant on business performance, (4) pricing capability has no effect on business performance. The results of this study have implications for hotel management to create added value for hotels, achieve competitive advantage and good business performance.Keywords: Business Performance, Human Capital, Pricing Capability, Relational Capital, Structural Capital